Alexithymia, resilience and suicidal ideation among patients with obsessive–compulsive disorder - Mai Mohamed Elsayed Abd-Elhamed; Rehab Fathy Abdel Hady; Shadia Fathy Mahmoud; Bothina Elsayed Said Mohamed (Middle East Current Psychiatry, 2023)
Abstract Background Obsessive–compulsive disorder (OCD) is a psychiatric illness with a considerable risk of alexithymia, and suicide may make this risk worse. This study aimed to assess alexithymia, resilience, and suicidal ideation among patients with obsessive–compulsive disorder. A cross-sectional study was established at the psychiatric outpatient clinic at Zagazig University Hospitals in addition to Abbasyia Hospital for Mental Health in Cairo City. A purposive sample of 140 obsessive–compulsive patients. Five tools were used for data collection, including the socio-demographic questionnaire, the Yale-Brown Obsessive Compulsive Scale (Y-BOCS), the Toronto Alexithymia Scale (TAS-20), the Resilience Scale, and the Scale for Suicidal Ideation (SSI). Results The study findings demonstrated that in excess of two-thirds of the studied subjects had mild obsessive–compulsive disorder, slightly more than two-thirds of them suffered from alexithymia, more than half of patients had a moderate level of resilience, and the majority of them had suicidal ideation. Patients’ obsessive–compulsive score was a statistically significant positive predictor for suicidal ideation. Conclusions A positive and significant correlation was found between patients’ obsessive–compulsive scores and both alexithymia and suicidal ideation scores. Negatively significant correlations were found between resilience and each patient’s obsessive–compulsive score, alexithymia, and suicidal ideation. Therefore, it is recommended implementing longitudinal studies to establish the causality between OCD Sufferers’ resilience, alexithymia, and ideations of suicide.